Erythrodermic Psoriasis: A Case Report - Peter Nugraha Soekmadji; Angelica Agnesia Rening; Aulia Okti Wulandari; Bherline Novita Wijaya; Destiya Ulfah Riany (Rumah Sakit Unggul Karsa Medika, 2023)
Psoriasis is a chronic, immune-mediated skin disorder that affects 1-3% of the population. It is believed to be caused by a combination of genetic and environmental factors such as trauma, infections, psychological stress, and certain medications. This disease has a strong genetic component and can persist for a lifetime, with repeated exacerbations and remissions that can have a significant impact on a person's emotional and physical well-being